Adaptive NK cell responses in HIV/SIV infections: a roadmap to cell-based therapeutics? - Ram, Daniel R. (J Leukoc Biol, 2019)
Natural killer cells play a critical role in antiviral and anti-tumor responses. While current NK cell immune therapies have focused primarily on cancer biology, many of these advances can be readily applied to target HIV/SIV-infected cells. Promising developments include recent reports that CAR NK cells are capable of targeted responses while producing less off-target and toxic side-effects than are associated with CAR T cell therapies. Further CAR NK cells derived from inducible pluripotent stem cells or cell lines may allow for more rapid ‘off-the-shelf’ access. Other work investigating the IL-15 superagonist ALT-803 (now N803) may also provide a recourse for enhancing NK cell responses in the context of the immunosuppressive and inflammatory environment of chronic HIV/SIV infections, leading to enhanced control of viremia. With a broader acceptance of research supporting adaptive functions in NK cells it is likely that novel immunotherapeutics and vaccine modalities will aim to generate virus-specific memory NK cells. In doing so, better targeted NK cell responses against virus-infected cells may usher in a new era of NK cell-tuned immune therapy.